The Great Firewall of China: Praktik Kebijakan Sensor Internet Pada Era Xi Jinping - R.Tuty Nur Mutia; Faqih Albiruni Yahya (Historia: Jurnal Pendidik dan Peneliti Sejarah, 2023)
Internet censorship policies refer to government actions in filtering and controlling what people can access on the internet. The Great Firewall of China (GFW) is a term that refers to the internet censorship policy implemented by the Chinese government. Since the development of the internet in the 1990s, the Chinese government has continued to exercise control over the internet through censorship. In the era of Xi Jinping's leadership, internet censorship policies continued to strengthen. Various matters relating to policy practice are the subject of this article. The research method used in this article is the historical method. The results of the study show that China is one of the countries that signed the International Convention on Civil and Political Rights in 1998, which includes the values of freedom of access to information and expression on the internet. Meanwhile, the practice of internet censorship policies in the Xi Jinping era was carried out in order to maintain China's sovereignty and build China as a world cyber power. However, it turns out that the practice of this policy is substantially not in accordance with the values of freedom as stated in the International Convention on Civil and Political Rights. Keywords: internet, censorship, Xi Jinping, The Great Firewall of China